Spontaneous Intracranial Hypotension Without CSF Leakage—Concept of a Pathological Cranial to Spinal Fluid Shift - Goldberg, Johannes; Häni, Levin; Jesse, Christopher Marvin; Zubak, Irena; Piechowiak, Eike I.; Gralla, Jan; Dobrocky, Tomas; Beck, Jürgen; Raabe, Andreas (Frontiers in Neurology, 2021)
Objective Spontaneous intracranial hypotension (SIH) is typically caused by CSF leakage from a spinal dural tear, a meningeal diverticulum, or a CSF venous fistula. However, some patients present with classic orthostatic symptoms and typical intracranial imaging findings without evidence of CSF leakage despite repeated diagnostic work-up. This article aims to elaborate a hypothesis that would explain a pathologically increased orthostatic shift of CSF from the cranial to the spinal compartment in the absence of a CSF leak. Medical Hypothesis The symptoms of SIH are caused by a decrease in intracranial CSF volume, intracranial hypotension, and downward displacement of intracranial structures. A combination of pathologically increased spinal compliance, decreased intracranial CSF volume, low CSF outflow resistance, and decreased venous pressure might result in a pathological orthostatic cranial-to-spinal CSF shift. Thus, in rare cases, intracranial hypotension may occur in the absence of CSF leakage from the dural sac. Conclusion We propose a pathophysiological concept for the subgroup of SIH patients with typical cranial imaging findings and no evidence of CSF leakage. In these patients, reducing the compliance or the volume of the spinal compartment seems to be the appropriate therapeutic strategy.